2016
DOI: 10.1016/j.aop.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Order-fractal transitions in abstract paintings

Abstract: We report the degree of order of twenty-two Jackson Pollock's paintings using Hausdorff-Besicovitch fractal dimension. Through the maximum value of each multi-fractal spectrum, the artworks are classify by the year in which they were painted. It has been reported that Pollock's paintings are fractal and it increased on his latest works. However our results show that fractal dimension of the paintings are on a range of fractal dimension with values close to two.We identify this behavior as a fractal-order trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Among the seminal works, we have the article by Taylor et al (20), where Pollock's paintings are characterized by an increasing fractal dimension over the course of his artistic career. This research article can be considered a landmark for the quantitative study of visual arts, inspiring many further applications of fractal analysis and related methods to determine the authenticity of paintings (21)(22)(23)(24)(25) and to study the evolution of specific artists (26,27), the statistical properties of particular paintings (28) and artists (29)(30)(31), art movements (32), and many other visual expressions (33)(34)(35). The most recent advances of this emerging and rapidly growing field of research are comprehensively documented in several conference proceedings and special issues of scientific journals (36)(37)(38), where contributions have been focusing also on artwork restoration tools, authentication problems, and stylometry assessment procedures.…”
mentioning
confidence: 99%
“…Among the seminal works, we have the article by Taylor et al (20), where Pollock's paintings are characterized by an increasing fractal dimension over the course of his artistic career. This research article can be considered a landmark for the quantitative study of visual arts, inspiring many further applications of fractal analysis and related methods to determine the authenticity of paintings (21)(22)(23)(24)(25) and to study the evolution of specific artists (26,27), the statistical properties of particular paintings (28) and artists (29)(30)(31), art movements (32), and many other visual expressions (33)(34)(35). The most recent advances of this emerging and rapidly growing field of research are comprehensively documented in several conference proceedings and special issues of scientific journals (36)(37)(38), where contributions have been focusing also on artwork restoration tools, authentication problems, and stylometry assessment procedures.…”
mentioning
confidence: 99%
“…But first applications happened only at the turn of the twenty-first century, where the work of Taylor et al [61] showed that Pollock's paintings are characterized by an increasing fractal dimension over the course of his artistic career. This subsequently inspired the application of fractal analysis to the authenticity of paintings [62][63][64][65][66], to the evolution of artists [67,68], to the statistical properties of paintings [69] and artists [70][71][72], to art movements [73] and to other visual expressions [74][75][76]. And we would be remiss not to mention that fractal art is a fascinating subject on its own right [77].…”
Section: Visual Artsmentioning
confidence: 99%
“…Several complexity indices have been adopted to analyze art, namely entropy [ 18 , 19 ], Kolmogorov complexity [ 20 , 21 ], fractal dimension [ 22 , 23 ], and others [ 24 , 25 ]. Such indices are not independent, but they capture different aspects of the system state, complementing each other and leading to a deeper assessment of the subject under study [ 26 ].…”
Section: Introductionmentioning
confidence: 99%